Elderly‐onset acute necrotizing encephalopathy mimicking severe heat stroke: a case report and review of the literature. Issue 3 (11th April 2019) - Odagiri, Arisa; Yamaoka, Ayumu; Miyata, Kei; Bunya, Naofumi; Kasai, Takehiko; Takeyama, Yoshihiro; Uemura, Shuji; Mikami, Takeshi; Narimatsu, Eichi
Abstract : Background: Acute necrotizing encephalopathy (ANE), known as influenza‐associated encephalitis, typically affects children. Case presentation: A 70‐year‐old woman was admitted to the hospital with altered consciousness, a high temperature, and severe hypotension. Computed tomography (CT) of the head showed no abnormalities; thus, a diagnosis of suspected severe heat stroke was made. On day 2, repeated head CT revealed bilateral symmetrical lesions to the thalamus, and a rapid influenza antigen test was positive. Based on the CT findings and the medical history of influenza, a differential diagnosis of ANE was made. Subsequently, brain edema spread across the whole brain, and the patient died on day 21. Conclusion: In elderly patients, differentiating ANE from severe heat stroke in a high‐temperature environment is difficult because of the similarities in clinical symptoms due to multiple organ failure. Abstract : Head computed tomography scan of a woman with suspected severe heat stroke revealed bilateral symmetrical thalamic lesions. Based on the computed tomography findings and medical history of influenza, she was diagnosed with acute necrotizing encephalopathy. Because of the similarities in clinical symptoms due to multiple organ failure, differential diagnosis of comatose acute necrotizing encephalopathy and severe heat stroke in a high‐temperature environment was difficult.